Jupiter's Influence on the Building Blocks of Mars and Earth. Issue 12 (29th June 2018) - Brasser, R.; Dauphas, N.; Mojzsis, S. J.
Abstract: Radiometric dating indicates that Mars accreted in the first ~4 Myr of the solar system, coinciding with the formation and possible migration of Jupiter. While nebular gas from the protoplanetary disk was still present, Jupiter may have migrated inward and tacked at 1.5 AU in a 3:2 resonance with Saturn. This migration excited planetary building blocks in the inner solar system, resulting in extensive mixing and planetesimal removal. Here we evaluate the plausible nature of Mars's building blocks, focusing in particular on how its growth was influenced by Jupiter. We use dynamical simulations and an isotopic mixing model that traces the accretion. Dynamical simulations show that Jupiter's migration causes the late stages of Earth's and Mars's accretion to be dominated by EC (enstatite chondrite)‐type material due to the loss of ordinary chondrite planetesimals. Our analysis of available isotopic data for Mars shows that it consists of approximately 68 % − 39 + 0 EC + 32 % − 0 + 35 ordinary chondrite by mass (2 σ ). The large uncertainties indicate that isotopic analyses of Martian samples are generally too imprecise to definitely test model predictions; in particular, it remains uncertain whether or not Mars accreted predominantly EC material in the latter stages of its formation history. Dynamical simulations also provide no definitive constraint on Mars's accretion history due to the great variety of dynamical pathways that the Martian embryo exhibits. The present work calls for new measurements of isotopic anomalies in Martian meteorites targeting siderophile elements (most notably Ni, Mo, and Ru) to constrain Mars's accretion history and its formation location. Plain Language Summary: We report the first results that attempt to obtain the compositional makeup of material that formed Mars through the successive stages of its accretion. We employ Monte Carlo computer models that mix together the listed three classes of primitive (chondrite) meteorites to derive a bulk composition of Mars. This final composition, and the successive stages of Mars's accretion, is constrained by the isotopic variations of specific elements in the red planet and that of the various meteorites. The isotopic constraints as they currently exist, however, are insufficient to account for the composition of Mars. We conclude that Mars' accretion history remains mysterious, so much so that further high‐resolution isotopic analyses are warranted. Key Points: We report the first results to obtain the compositional makeup of material that formed Mars through the successive stages of its accretion Mars initially accreted a high fraction of ordinary chondrite material, which subsequently diminished as the planet grew Insufficient data from isotopic anomalies recorded in Martian meteorites mean that we still do not understand how Mars formed